Bakhtin and the Movies - Flanagan, M. author. aut Link
XI, 239 p.
Keywords: Martin Flanagan uses Bakhtin's notions of dialogism, chronotope and polyphony to address fundamental questions about film form and reception, focussing particularly on the way cinematic narrative utilises time and space in its very construction.